Pentingnya Pemahaman Motivasi Diri Sebagai Upaya Pencegahan Kemalasan Sosial Pada Warga Belajar PKBM Cipta Cendekia Cipondoh Kota Tangerang : Pentingnya Pemahaman Motivasi Diri sebagai Upaya pencegahan kemalasan sosial - Ahmad Nazir, Nazir; Achmad Nur Sholeh; Nefo Indra Nizar (STIT Darul Fattah Bandar Lampung, 2024)
The aim of this PKM is to find out how to understand self-motivation, how to prevent social laziness, how to understand self-motivation as an effort to prevent social laziness among students studying PKM Cipta Scholar Cipondoh. When carrying out observations or the results of observations that we have carried out, namely PKBM Cipta Scholar as a place for learning and teaching for those who have dropped out of school located in Cipondoh, Tangerang City, which is based on character education for underprivileged students who need support and self-motivation. in order to prevent social laziness from occurring. The mechanism used in PKM activities is through the question and answer lecture method, training and mentoring to students and alumni who want to learn and understand self-motivation in preventing social laziness. The training that will be produced in this PKM activity includes: providing knowledge and understanding about self-motivation as an effort to prevent social laziness that occurs among residents studying PKBM Cipta Ilmu Cipondoh Tangerang City.